Case Report: Inherited chromosomally integrated HHV-6B in a pediatric medulloblastoma patient with encephalitis - Sun, Scott; Knox, Konstance; Romashko, Alexander; Kundu, Madhu; Zhu, Haiying; Huang, Meei-Li; Malicki, Denise M.; Crawford, John R. (Frontiers in Immunology, 2025)
BackgroundHuman herpesvirus 6B (HHV-6B) is associated with various central nervous system (CNS) disorders, particularly in immunocompromised patients. We present a rare case of inherited chromosomally integrated HHV-6B (iciHHV-6B), also referred to as endogenous HHV-6B (eHHV-6B) discovered during the workup for encephalitis in a child with relapsed non-WNT/non-SHH medulloblastoma.Case presentationA preschool aged female was treated in infancy for non-WNT, non-SHH medulloblastoma with high dose chemotherapy and autologous stem cell transplant. She had leptomeningeal recurrence 6 months after transplant and received salvage therapy with high dose craniospinal proton therapy. Six months following radiation, she developed high fever, acute encephalopathy and seizures. Neuroimaging revealed left posterior temporal gyral edema, while extensive infectious/paraneoplastic/autoimmune workup demonstrated markedly elevated HHV-6B viral loads, consistent with inherited chromosomally integrated HHV-6B (iciHHV-6B) which was confirmed through blood digital droplet PCR analysis and PCR-based nail clipping analysis demonstrating paternal inheritance. Retrospective immunohistochemical analysis of the original medulloblastoma revealed HHV-6 late structural glycoprotein H antigens in peritumoral lymphocytes. Serum HHV-6 U100 glycoprotein mRNA detection was consistent with iciHHV-6B. Treatment included intravenous immunoglobulin (IVIG) and ganciclovir followed by a 12-month course of IVIG monotherapy with clinical improvement.ConclusionOur case highlights the diagnostic challenges, controversies and clinical implications of ici-HHV-6/eHHV-6 in immunocompromised patients with encephalitis, where qualitative CSF viral detection alone may be insufficient for accurate diagnosis and cannot identify ici-HHV-6 status which complicates treatment decisions. This case demonstrates the importance of multimodal testing including chromosomal integration analysis in patients with high HHV-6 viral loads.